Sospeso tra due mondi: il velo di San Giusto tra Bisanzio e Trieste (Fenestella. Inside Medieval Art, 2021)
This article aims to a preliminary reassessment of the silk veil preserved in the Treasury of Trieste cathedral. The cloth is unparalleled in Byzantine as well in western medieval art, in that it is painted with tempera on both sides. It depicts a youthful martyr in a court costume, and bears an inscription that identifies the saint as St. Just. Since its alleged recovery from a reliquary in the early nineteenth century, the cloth has been often addressed by the scholars, who ascribed it either to a Byzantine or to a local master and dated it between the eleventh and the fourteenth century.Despite being referred to in several more general studies, it has been rarely considered individually. In this paper I address the many questions that the Trieste veil raises, including problems of chronology, provenance, function, and iconography. After careful observation and based on both primary sources and visual evidence, I argue that it was produced in Byzantium, possibly at an early date, to serve as a liturgical implement; later, it was brought to the West, where the saint was given a new identity and the cloth was reused as a banner after being painted on the reverse.
Keywords: Byzantine Art; Trieste; St. Just; Painted clothes; Medieval Painting; Silk; Medieval Iconography